Diarrhoea in critical care patients: focus on special issues - Maurizio Ventrucci; Paolo Pozzato (Italian Journal of Medicine, 2013)
BACKGROUND Diarrhoea is common in critically ill patients, especially in elderly subjects during antibiotic therapy and enteral feeding. The management of diarrhoea includes generous hydration, compensation for the loss of electrolytes, antidiarrhoeal oral medications, and antibiotic drugs in infections related diarrhoea. AIM OF THE STUDY The purpose of this review is to provide an update on particular types of diarrhoea in critically ill patients. Epidemiological data will be discussed, with special emphasis on Clostridium difficile-associated diarrhoea. The possible therapeutic measures will be presented.